PAMELA ANDERSON AND "VULNERABILITY". Issue 1 (3rd March 2020) - Montefiore, Alan
Abstract: I first met Pamela way back in the 1980s, when I found myself acting as supervisor of her doctoral thesis on the philosophy of Paul Ricoeur. As I read her later writing and look back on her career, I am most struck by, on the one hand, the marked contrast between the vulnerability and uncertainties, both philosophical and personal, of her earlier time and the assurance of her later writing; and, on the other, the persistence throughout the continuing narrative of her life of an essential interconnection between her deepest philosophical and personal concerns. These include, most notably, the importance of taking, each of us, one's sense of one's own vulnerability not as a reason for the construction of walls behind which to shelter from others but rather as a base from which to reach out to them in a spirit of what Pamela did not hesitate to call "love."